Pengaruh Literasi Keuangan, Pendapatan, Perilaku Keuangan, serta Persepsi Risiko Terhadap Keputusan Investasi pada Generasi Z di Kota Surabaya. - Astutik, Eka Yuli; Sriyono, Sriyono; Kumalasari, Herlinda Maya (Universitas Respati Indonesia, 2024)
The purpose of this research is to find out Generation Z's investment decisions in Suabaya City. This research analyzes financial literacy towards Generation Z investment decisions, income towards Generation Z investment decisions, financial behavior towards Generation Z investment decisions, and also risk perceptions towards Generation Z investment decisions. The method in this research uses quantitative methods with data collection techniques using Purposive techniques Sampling with certain criteria that are met. The sample in this study consisted of 100 respondents. Data collection in this research was by distributing questionnaires to respondents using Google Form. Software called SPSS V26 is used for the analysis process. Data analysis techniques include testing standard assumptions and multiple linear regression analysis. In hypothesis testing, the R2 test and t test are used. The results of this research show that there is a negative influence on the financial literacy variable, and a positive influence on the income, financial behavior and risk perception variables on investment decisions with (t table value > 1.661), and partially risk perception has a strong impact on investment decisions in Generation Z in Surabaya City.